(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
As a result of the world globalization process in the modern world, many peoples are losing their specific features, regional cultural differences. This situation raises interethnic, interfaith relations to the forefront in most regions of the world. With the wave of democratization and independence, international relations have become complicated and the geopolitical picture in Central Asia has changed. In this regard, the study of the history of ethnopolitical and cultural relations of this or that nation is an overriding task facing scientists. Today, in the context of the aggravation of the national question, the study of the history of relations between peoples is very relevant, since many works have appeared in which the historical process is distorted in favor of nationalist aspirations, the exclusiveness of individual nations or ethnic groups is artificially promoted, and sometimes the role and place in the history of this or that people is deliberately underestimated.